Essentials of anatomy and physiology - Tortora, Gerard J.; Bryan Derrickson (Singapore : Wiley, 2003)
The Ninth edition of Tortora's Introduction to the Human Body provides basic content, focused design, and relevant connections about the essentials of anatomy and physiology. All chapters are focused on the essential structure and functions of the human body needed for a basic understanding of homeostasis.
Chapter 1. Organization of the Human Body -- Chapter 2. Introductory Chemistry -- Chapter 3. Cells -- Chapter 4. Tissues -- Chapter 5. The Integumentary System -- Chapter 6. The Skeletal System -- Chapter 7. Joints -- Chapter 8 . The Muscular System -- Chapter 9. Nervous Tissue -- Chapter 10. Central Nervous System, Spinal Nerves, and Cranial Nerves -- Chapter 11. Autonomic Nervous System -- Chapter 12. Somatic Senses and Special Senses -- Chapter 13. The Endocrine System -- Chapter 14. The Cardiovascular System: Blood -- Chapter 15. The Cardiovascular System: Heart -- Chapter 16. The Cardiovascular System: Blood Vessels and Circulation -- Chapter 17. The Lymphatic System and Immunity -- Chapter 18. The Respiratory System -- Chapter 19. The Digestive System -- Chapter 20. Nutrition and Metabolism -- Chapter 21. The Urinary System -- Chapter 22. Fluid, Electrolyte, and Acid-Base Balance -- Chapter 23. The Reproductive Systems -- Chapter 24. Development and Inheritance.
Includes index.
Keywords: HUMAN PHYSIOLOGY